POLITICAL CAMPAIGN STRATEGY OF PDIP IN SURABAYA ON INSTAGRAM AND FACEBOOK MEDIA - Nur Fatimatuz Zahroh (JWP (Jurnal Wacana Politik), 2023)
This study describes the important role of social media in politics in interacting with digital networks. Eri – Armudji further highlight the advantages of PDIP in order to gain promotional votes on Instagram and Facebook media with embedded text in various forms of campaign content to field implementation. PDIP brings Eri – Armudji as a leader in the City of Surabaya 2020-2024. This study uses descriptive qualitative, data collection through interviews, documentation, and observation. The theoretical approach uses Niffenegger’s political strategy of 4P (Product, Promotion, Prince, Place). Research results, First; shows that the success of PDIP Surabaya as a political party has a high correlation with figures, community members in increasing their popularity and electability through coalitions of parliamentary and non-parliamentary parties to the use of social media. One of them continues to introduce Eri – Armudji by carrying out campaign movements through the 4P strategy that has been proven to win the superior vote of 597,540 voters or 56.94% of political opponents. Second; Eri – Armudji’s political campaign during the pandemic used a candidate platform approach, humanist-religious, economic value, mass communication skills both in the field and in social media as a means of winning political campaigns online with of followers of Eri Cahyadi on Instagram 26,000 – Facebook 6,695, while followers Armudji on Instagram 19,700 – Facebook 1,205. So that social media has an effect on increasing victories of Eri Cahyadi and Armudji with a cross-party coalition strategy approach and strengthening the acquisition of parliamentary seats in the DPRD in the city of Surabaya.